Methods of implementing interdisciplinary links between physics and computer science (Journal of Educational Sciences, 2021)
The article discusses issues related to the training of future teachers through the implementation of a transdisciplinary approach to teaching physics in tandem with computer science. The research project is analyzed as the main method contributing to the successful mastery of physics and computer science by future teachers. General principles and criteria for the selection of educational material for an educational program of teaching physics in tandem with computer science have been developed. The stages of effective teaching physics together with computer are presented. Recommendations on for the implementation of interdisciplinary connections in teaching physics in tandem with computer science for the preparation of future teachers have been developed.The connections between knowledge and the educational process in the preparation of future teachers of the physics course through the actualization of interdisciplinary connections and the development of skills to diversify the application of the knowledge gained are considered. The modern stage of development of science is characterized by interdisciplinary connections, meta-interaction of sciences, therefore the relevance of intersubject and intrasubject connections in the educational process is quite high. This contributes to the generalization and deepening of students' competencies in the development of skills of independent cognitive activity. Accordingly, intersubject and intrasubject connections are the most important condition and result of an integrated approach in teaching students. The methodology and the peculiarity of its application for students in the study of information-physical disciplines are disclosed, a theoretical basis for constructing a system of tasks is given.Keywords: physics, informatics, methods, research project, modelling, cross-curricular connections, approach, principles.